2023
DOI: 10.3390/cancers15215168
|View full text |Cite
|
Sign up to set email alerts
|

Heparan-6-O-Endosulfatase 2 Promotes Invasiveness of Head and Neck Squamous Carcinoma Cell Lines in Co-Cultures with Cancer-Associated Fibroblasts

Pritha Mukherjee,
Xin Zhou,
Julius Benicky
et al.

Abstract: Local invasiveness of head and neck squamous cell carcinoma (HNSCC) is a complex phenomenon supported by interaction of the cancer cells with the tumor microenvironment (TME). We and others have shown that cancer-associated fibroblasts (CAFs) are a component of the TME that can promote local invasion in HNSCC and other cancers. Here we report that the secretory enzyme heparan-6-O-endosulfatase 2 (Sulf-2) directly affects the CAF-supported invasion of the HNSCC cell lines SCC35 and Cal33 into Matrigel. The Sulf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…We recently reported a Sulf-2 dependent spheroid invasion model consisting of a co-culture of SCC35 cancer cells with a primary cancer associated fibroblast (HNCAF37) in Matrigel (Mukherjee et al, 2023). We have shown that Sulf-2 KO SCC35 cells invade Matrigel in this system significantly less than the wild type SCC35 cells.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported a Sulf-2 dependent spheroid invasion model consisting of a co-culture of SCC35 cancer cells with a primary cancer associated fibroblast (HNCAF37) in Matrigel (Mukherjee et al, 2023). We have shown that Sulf-2 KO SCC35 cells invade Matrigel in this system significantly less than the wild type SCC35 cells.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown previously that the marine fucosylated chondroitin sulfate HfFucCS, a newly identified inhibitor of heparan 6-O-endosulfatase SULF2, is an inhibitor of HNSCC tumor cell invasion [34]. We treated the SCC35 cells with a combination of the MO-I-1151 and HfFucCS inhibitors to see if they together inhibit the invasion more efficiently (Figure 4A).…”
Section: Combination Of Mo-i-1151 With Hffuccs Has An Additive Effect...mentioning
confidence: 97%
“…We used a Matrigel-embedded co-culture spheroid model of SCC35 tumor cells with CAF 61137, optimized previously [34], to evaluate the impact of MO-I-1151 on cell invasion (Figure 3A). The CAF-supported tumor cell invasion was recorded on day 5, and our results show that MO-I-1151 reduced the area of the co-culture spheroids by 44% (p < 0.0001) for MO-I-1151 Low and 45% (p < 0.0001) for MO-I-1151 High (Figure 3B) compared to the untreated controls.…”
Section: Mo-1151 Inhibits Caf-mediated Invasion Of Spheroids In Matrigelmentioning
confidence: 99%
See 2 more Smart Citations